District-Level Primary Care Supply Buffers the Negative Impact of Functional Limitations on Illness Perceptions in Older Adults with Multiple Illnesses. Issue 3 (22nd November 2014) - Schüz, Benjamin; Tesch-Römer, Clemens; Wurm, Susanne
Abstract: Background: Illness perceptions predict important outcomes, e.g. coping, adherence and well-being. Less is known about the sources of illness perceptions, in particular the role of environmental factors such as primary care supply. Purpose: This study examines whether and how primary care supply (on district level) affects individual illness perceptions. Methods: We conducted a longitudinal study in 271 adults 65 years and older with multiple illnesses. Functional limitations (SF-36 physical functioning subscale) at time 1 were tested as predictors of illness perceptions 6 months later. Primary care supply on district level was matched to individual data. Results: In multilevel models, functional limitations predicted illness perceptions. Primary care supply on district level moderated the impact of functional limitations on individual identity and emotional response perceptions, with better supply buffering detrimental effects of functional limitations. Conclusions: Illness perceptions do not only depend on individual factors, but socio-structural factors also substantially contribute to individual illness perceptions.